Pengembangan Modul Statistika sebagai Media Penunjang Mata Kuliah Institusi di IKIP Budi Utomo Malang - Rina Wijayanti; Siti Napfiah (IKIP Budi Utomo Malang, 2016)
This research aims to produce products such as module, which supporter statistics courses in IKIP Budi Utomo Malang institutions. It can be used to enhance the students' ability to solve problems. This research development method using ADDIE models which include analysis, design, development, implementation, evaluation. Methods of data collection in this study include legibility test. Results of this study we concluded the step wrote statistics module that determining competency standards, specify the title of the module, arrange the contents of the module, cover design, legibility test, revision and production. Based on the conclusion that thelegibility test for aspects of language, presentation, and graphic declared valid while the worthiness aspect of the module is very valid. So based on student legibility test module does not need to be revised.